Lags in the effects of monetary policy : a nonparametric analysis - Uselton, Gene C. (New York : M. Dekker, 1974)
This book is a study undertaken in an effort to determine the best possible estimate of time lag between economic action and effect. Beginning with the assumption that fluctuations in the supply of money exert significant influence on such economic aggregates as gross national product, general business conditions, and price levels, the author investigates the crucial importance of the Federal Open Market Committee's policy decisions to the promotion of high employment levels, stable prices, sustainable growth, and balance-of -payments equilibrium.
Includes indexes.
Bibliography: p. 161-166.
usc 07/07/2017
Loans
Keywords: Monetary policy; Economic lag